2008
DOI: 10.1175/2008jamc1890.1
|View full text |Cite
|
Sign up to set email alerts
|

A Cloud and Precipitation Feature Database from Nine Years of TRMM Observations

Abstract: An event-based method of analyzing the measurements from multiple satellite sensors is presented by using observations of the Tropical Rainfall Measuring Mission (TRMM) precipitation radar (PR), Microwave Imager (TMI), Visible and Infrared Scanner (VIRS), and Lightning Imaging System (LIS). First, the observations from PR, VIRS, TMI, and LIS are temporally and spatially collocated. Then the cloud and precipitation features are defined by grouping contiguous pixels using various criteria, including surface rain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
327
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 337 publications
(343 citation statements)
references
References 32 publications
13
327
0
3
Order By: Relevance
“…[10] During 1998-2011, more than 28 million RPFs and 21 million CFs are identified from the TRMM PR observations over 36 S-36 N, most of which are over the ocean ( Table 1 RPFs and CFs are similar to and consistent with past studies [Nesbitt et al, 2000;Liu et al 2008] and are not shown here. We mainly focus on describing the properties of the CFs with large areas in the following sections.…”
Section: Global Distribution Of Organized Convectionsupporting
confidence: 77%
See 1 more Smart Citation
“…[10] During 1998-2011, more than 28 million RPFs and 21 million CFs are identified from the TRMM PR observations over 36 S-36 N, most of which are over the ocean ( Table 1 RPFs and CFs are similar to and consistent with past studies [Nesbitt et al, 2000;Liu et al 2008] and are not shown here. We mainly focus on describing the properties of the CFs with large areas in the following sections.…”
Section: Global Distribution Of Organized Convectionsupporting
confidence: 77%
“…After recording the general information of RPF size (total pixel numbers), mean rain rate, convective rain contribution, etc., the convective intensity proxies for each PF, such as minimum 85 GHz polarization corrected temperature (PCT) [Spencer et al, 1989] estimated from TRMM Microwave Imager observed radiance, the maximum heights of PR 30 and 40 dBZ, and flash counts observed by the TRMM Lightning Imaging Sensor for each RPF, are analyzed. Additional information on the RPF database and its uses can be found in Liu et al [2008]. Using similar methodology, the convective features (CFs) are identified by grouping the contiguous pixels with convective precipitation that are categorized by the PR rain type algorithm [Awaka et al, 1998.…”
Section: Methodsmentioning
confidence: 99%
“…Other things being equal, updrafts over land are likely to have higher supercooled liquid water contents than over ocean, where cloud water is converted to rain more quickly and depletes cloud water more efficiently before the updraft reaches the mixed-phase region. Also, the greatest difference between land and ocean in Figure 7 is in the temperature range of −5°C to −8°C (∼6 km), above which oceanic clouds often have a very rapid decrease in reflectivity with altitude compared with continental clouds [Zipser and Lutz, 1994;Liu et al, 2008], so it is possible that many of the oceanic (land) systems with large areas of 35 dBZ echo at −6°C have smaller (larger) area of 35 dBZ at −10°C to −15°C where charge separation is more likely.…”
Section: Discussionmentioning
confidence: 99%
“…[13] This study is based on precipitating features (storm scale), using the 11 years long TRMM precipitation feature (PF) database [Nesbitt et al, 2000;Liu et al, 2008]. Lightning data are from observations by the TRMM LIS, while thunderstorm parameters are based on measurements from the TRMM precipitation radar (PR) and microwave imager (TMI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation